THE VALUE OF NATIVE TONGUE IN PROFESSIONAL ACTIVITY - Kardelienė, Laimutė; Kardelis, Kęstutis (Acta Paedagogica Vilnensia, 2013)
When highlighting the impact of globalization as a controversial concept in the process of teaching the native tongue, the present article focuses on the value of the native tongue in the professional activity of a pedagogue. The responsibility of the lecturer of a specific subject as an educator of the native tongue concerning the use of the native tongue in the context of the peculiarities of fulfilling this role in the professional activity is highlighted. The obtained empirical data have revealed that teachers of physical education more favourably evaluate of teachers-educators rather than teachers of physical education as improvers of the native tongue and promoters of ethnic identity. A presupposition is made that the athletic biography of teachers and their former experience as students in the lessons of physical education have an impact on their attitude towards the knowledge of their native tongue and its skills in professional activity.
Keywords: globalization; native tongue; knowledge of teachers of physical education in the field of the native tongue; skills and abilities of teachers of physical education in professional activity